No pain, no gain: can a supply network become stronger following a disruption? - Picasso, Fernando Gonçalves (2021)
Supply network disruptions have gained increasingly attention as governments, financial experts and the average consumer had their daily lives affected by Covid-19. The literature on supply network disruption has provided substantial knowledge about supply network resilience, that is, how a supply network can recover from a disruption to return to its pre-disruption level of operation. However, recent cases have demonstrated that supply networks can recover stronger following a supply network disruption. Thus, our research question focuses on whether supply networks can leverage a supply network disruption to recover stronger than before. We build on metaphorical transfer to develop our theoretical foundations. Using hypertrophy through muscle recovery as the source phenomena, we develop the concept of hyper-resilient supply network. We further develop this concept through case research methodology. Our findings discuss the mechanisms through which supply networks can recover stronger following a supply network disruption. We contribute to the supply network resilience literature by demonstrating that supply networks can use mechanisms to respond to supply network disruptions that go beyond resilience.